Multidimensional Evaluation Of Analogical Modeling On Sociocultural Dynamics And Learning Context - Polat, Mehmet; Canpolat, Erdal (My University, 2025)
This study aims to analyze the relationship between sociocultural dynamics and learning contexts and the analogical modeling produced by middle school students in the process of making sense of the concept of “matter” in a multi-layered way. In the study conducted with 189 fifth grade students studying in project/private, urban public and village public schools in Elazığ, students were asked to complete the statement “Matter is like ... because ...” and the data were analyzed with MAXQODA 2022 and SPSS within the framework of school type, residential unit, family education level and income status variables. The findings showed that analogies differed depending on sociocultural status: Rural school students produced analogies based on concrete environmental experiences (agriculture, nature), while private school students developed abstract systems (mathematical models) and interdisciplinary metaphors. While conceptual depth and scientific language were evident in students with higher parental education and income, the analogies generated by the students from low socioeconomic groups were limited to everyday activities. In line with Bourdieu's cultural capital theory, analogies are understood to be pedagogical reflections of social inequalities. For inclusion in education, it is recommended to consider the sociocultural context in curriculum design and to diversify teaching strategies.
Keywords: Science education; analogical modelling; sociocultural inequalities